Thermoelectric Properties of Arsenic Triphosphide (AsP3) Monolayer: A First-Principles Study - Fan, Liangshuang; Yang, Hengyu; Xie, Guofeng (Frontiers in Mechanical Engineering, 2021)
Recently, monolayer of triphosphides (e.g., InP3, SnP3, and GaP3) attracts much attention due to their good thermoelectric performance. Herein, we predict a novel triphosphide monolayer AsP3 and comprehensively investigate its thermoelectric properties by combining first-principles calculations and semiclassical Boltzmann transport theory. The results show that AsP3 monolayer has an ultralow thermal conductivity of 0.36 and 0.55 Wm K−1 at room temperature along the armchair and zigzag direction. Surprisingly, its maximum Seebeck coefficient in the p-type doping reaches 2,860 µVK−1. Because of the ultralow thermal conductivity and ultrahigh Seebeck coefficient, the thermoelectric performance of AsP3 monolayer is excellent, and the maximum ZT of p-type can reach 3.36 at 500 K along the armchair direction, which is much higher than that of corresponding bulk AsP3 at the same temperature. Our work indicates that the AsP3 monolayer is the promising candidate in TE applications and will also stimulate experimental scientists’ interest in the preparation, characterization, and thermoelectric performance tuning.